Plasma Membrane Localization Is Essential for Oryza sativa Pto-Interacting Protein 1a-Mediated Negative Regulation of Immune Signaling in Rice . Issue 1 (23rd June 2014) - Matsui, Hidenori; Fujiwara, Masayuki; Hamada, Satoshi; Shimamoto, Ko; Nomura, Yuko; Nakagami, Hirofumi; Takahashi, Akira; Hirochika, Hirohiko
Abstract : Appropriate complex formation at the plasma membrane is indispensable for a negative regulator of immune signaling in rice . Abstract: Oryza sativa Pto-interacting protein 1a (OsPti1a), an ortholog of tomato ( Solanum lycopersicum ) SlPti1, functions as a negative regulator of innate immunity in rice ( Oryza sativa ). In ospti1a mutants, the activation of immune responses, including hypersensitive response-like cell death, is caused by loss of the OsPti1a protein; however, it is as yet unclear how OsPti1a suppresses immune responses. Here, we report that OsPti1a localizes to detergent-resistant membrane fractions of the plasma membrane through lipid modification of the protein's amino terminus, which is highly conserved among Pti1 orthologs in several plant species. Importantly, mislocalization of OsPti1a after deletion of its amino terminus reduced its ability to complement the mutant phenotypes, including hypersensitive response-like cell death. Furthermore, complex formation of OsPti1a depends on its amino terminus-mediated membrane localization. Liquid chromatography-tandem mass spectrometry analysis of OsPti1a complex-interacting proteins identified several defense-related proteins. Collectively, these findings indicate that appropriate complex formation by OsPti1a at the plasma membrane is required for the negative regulation of plant immune responses in rice.